2014
DOI: 10.4103/1817-1737.140134
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT rarely provides additional information other than primary tumor detection in patients with pulmonary carcinoid tumors

Abstract: AIM:The purpose of this study was to assess the contribution of 18F-fluorodeoxyglucose (FDG) Positron Emission Tomography (PET)/Computed Tomography (CT) in detection and staging of pulmonary carcinoid tumors.METHODS:A total of 22 patients with pulmonary carcinoid tumors (14 typical, 8 atypical) were reviewed in this retrospective study. PET/CT images of all patients were evaluated for primary tumor as well as metastatic regional lymph nodes, bone and other distant metastases. PET/CT positivity of primary tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 20 publications
3
21
1
Order By: Relevance
“…It is reported 18F-FDG PET-CT may be effective in early diagnosis of TPC, but this issue is controversial at present. [ 13 ] However, in our case, the ectopic source was located in middle lobe of right lung and it is quite difficult to distinguish with other pulmonary nodules on CT scan, such as intrapulmonary lymph nodes. The character of the nodule was defined by FDG PET-CT.…”
Section: Discussionmentioning
confidence: 66%
“…It is reported 18F-FDG PET-CT may be effective in early diagnosis of TPC, but this issue is controversial at present. [ 13 ] However, in our case, the ectopic source was located in middle lobe of right lung and it is quite difficult to distinguish with other pulmonary nodules on CT scan, such as intrapulmonary lymph nodes. The character of the nodule was defined by FDG PET-CT.…”
Section: Discussionmentioning
confidence: 66%
“…However, the studies by Erasmus et al and Krüger et al were limited by their size (7 and 13 patients, respectively) 13,15 . 18 F-FDG PET/CT is considered less well suited for imaging of neuroendocrine tumours with low proliferation rate, such as PCs 13,[20][21][22] . PCs are slow growing and their generally discrete 18 F-FDG uptake may lead to false-negative results.…”
Section: F-fdg Pet/ctmentioning
confidence: 99%
“…Some authors have reported that atypical carcinoids exhibited signi cantly higher FDG uptake than did typical carcinoids [16][17][18][19]. Tatci et al also observed a higher SUV max for atypical carcinoids than for typical carcinoids, although the difference was not statistically signi cant [20]. Fink et al analysed the clinicopathological data and outcomes of 142 patients with pulmonary carcinoids (128 typical and 14 atypical) and found that atypical carcinoids were associated with higher rates of nodal involvement and distant metastases [21].…”
Section: Discussionmentioning
confidence: 99%